Sustainability reporting in Malaysia-the extent and quality - Sheikh Abu Bakar, Aishah; Mohd Ghazali, Nazli Anum; Ahmad, Maslina (Human Resource Management Academic Research Society (HRMARS), 2019)
The objective of this study is to examine the extent and quality of sustainability reporting (SR) of Malaysian listed companies after Bursa Malaysia has launched its Sustainability Framework in 2015. The framework comprised amendments to the Listing Requirements (paragraph 29, part A of Appendix 9C, Main Market LR and practice note 9, Main Market) and the issuance of a Sustainability Reporting Guide (SRG) and Toolkits. The SRG provides more specific guidance on “what” and “how” sustainability information should be disclosed by the companies in their SR. The data was collected from the largest 100 listed companies’ annual reports for the year-end on and after 31 December 2016. The study applied content analysis method in collecting the data by using the disclosure checklist. The results show that the overall score for extent and quality of information are still low and companies in oil and gas industry disclosed most extent and of highest quality compared to other companies from other industries. In addition, it appears that companies disclose more on economic dimension which includes information regarding how their business operations influence and contribute to the other organizations and community economically, such as how much their procurement for local suppliers, how they contribute to socio-economic of the community and local people and how they give indirect economic impacts toward community. However, most of the information disclosed is qualitative and narrative statement rather than quantitative information.